TO STUDY THE EFFECTIVENESS OF BUTEYKO BREATHING TECHNIQUE VERSUS DIAPHRAGMATIC BREATHING IN ASTHMATICS (International Journal of Physiotherapy, 2014)
Background:Asthma is one of the most common chronic diseases in the world. It is estimated that around 300 million people in the world currently have asthma In Asthmatics dysfunctional breathing pattern is common. Breathing pattern is the basis of abnormal patterns in asthma. The purpose of this study was to find out the effectiveness of Buteyko breathing technique versus diaphragmatic breathing in asthmatics.Methods: 46 patients with asthma aged 20-65 years were taken. The duration of the study was 2 weeks & data was collected on day zero and at the end of 2nd week. The subjects were divided into two groups A & B 23 patients of asthma in each group were distributed by convenient sampling. Each subject was assessed according to FEV1, FEV1/FVC and PEFR Statistics were applied by using SPSS 11.Results: Results were calculated by using 0.05 level of significance. On the basis of above statistical analysis the p value for group A is less than 0.05. So the intervention on group A is effective than intervention on group B.Conclusion: So Buteyko breathing technique proves to be more effective than diaphragmatic breathing technique in asthmatics.